Effects of high-intensity interval training on food intake, retroperitoneal adipose tissue, and lipid profile in wistar rats: interactions with age and diet composition - Jimenes, Diogo Rodrigues; Teixeira Júnior, Nilton Rodrigues; Piovan, Silvano; Silva, Demis Roger da; Silva, Juliana Corá da; Rinaldi, Wilson; Barbosa, Carmem Patrícia (Journal of Physical Education (Maringá), 2025)
The relationship between diet, exercise, and health is well-studied due to its impact on metabolic balance and chronic disease prevention. Diets high in fat (e.g., HFD) are linked to obesity, while HIIT is known to improve body composition. Age adds complexity to the body’s response to diet and exercise because of physiological changes over time. This study aimed to examine the effects of HIIT on food and water intake and lipid profiles across different ages and diets in male Wistar rats, some of whom received an HFD. They were divided into sedentary and trained groups, with weekly assessments of water and food consumption. After 8 weeks of HIIT, animals were euthanized, and blood was collected for lipid analysis, along with liver and retroperitoneal fat samples. Elderly animals showed significant reductions in food intake during HIIT (p<0.0001), and although body mass increased with age (p<0.0001), HIIT reduced body mass and retroperitoneal fat across diets (p<0.0001). HIIT also decreased total cholesterol and triglycerides more effectively in adults and middle-aged animals (p<0.0001). These findings highlight the importance of age considerations in experimental designs, especially when incorporating intense exercise like HIIT.